2017
DOI: 10.1016/j.jpsychires.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Association between change in brain gray matter volume, cognition, and depression severity: Pre- and post- antidepressant pharmacotherapy for late-life depression

Abstract: Late-life depression (LLD) is associated with cognitive impairments and reduced gray matter volume (GMV); however the mechanisms underlying this association are not well understood. The goal of this study was to characterize changes in depression severity, cognitive function, and brain structure associated with pharmacologic antidepressant treatment for LLD. We administered a detailed neurocognitive battery and conducted structural magnetic resonance imaging (MRI) on 26 individuals with LLD, pre-/post-a 12-wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Of the 33 T1 studies, 7 used a longitudinal design in participants with LLD and an HC group or LLD only [ 26 32 ]. Four of these studies reported significant positive associations between the bilateral hippocampal volumes and changes in the Mini-Mental State Examination (MMSE) scores during follow-up periods lasting from 21 months to 4 years [ 27 , 30 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 33 T1 studies, 7 used a longitudinal design in participants with LLD and an HC group or LLD only [ 26 32 ]. Four of these studies reported significant positive associations between the bilateral hippocampal volumes and changes in the Mini-Mental State Examination (MMSE) scores during follow-up periods lasting from 21 months to 4 years [ 27 , 30 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…These studies also evaluated the relationship between GM volumes and specific cognitive domains including tests of processing speed [ 27 ], visuospatial memory [ 26 ], response inhibition and set-shifting [ 26 ], and verbal fluency and memory [ 29 ]. Hou et al (2012) showed that larger right hippocampal volume predicted improved performance on the Symbol Digit Modalities Test over a 21-month period [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…The extent of thinner cortical thickness in the SMA at baseline may predict improved SSRI response in MDD (Wu et al 2022b ). LLD is associated with CI and reduced gray matter volume (GMV), which, after a 12-week antidepressant pharmacotherapy, in the superior orbital frontal gyrus was associated with less improvement in depression severity, and increased GMV in the same region was associated with greater improvement in depression severity (Droppa et al 2017 ). Furthermore, after citalopram treatment in LLD, improvement of mood and cognition were associated with higher GMV in primary frontal areas and normalization of glucose metabolism in these brain regions (Marano et al 2015 ).…”
Section: Brain Changes Following Lld Treatmentmentioning
confidence: 99%
“…Age-related brain atrophy with a reduction in GMV has also been indicated in older adults with cognitive impairment [ 16 , 17 , 18 , 19 , 20 ]. Positive responses to antidepressant treatment in depression have led to increases in GMV along with improvements in depression severity [ 21 , 22 , 23 ]. Furthermore, orbitofrontal volume can distinguish non-remitted from remitted patients with depression, suggesting a neurobiological prediction model of GMV for GD [ 24 ].…”
Section: Introductionmentioning
confidence: 99%